Integration brings convergence? The role of public and human capital - Maria Jesus Delgado Rodriguez; Inmaculada Alvarez Ayuso (European Regional Science Association (ERSA), 2004)
This work decompose labor-productivity grotwh and convergence in EU into components attributable to technological change (shifts in the European production frontier), technological catch-up (movements toward or away from the frontier) and factor accumulation (movement toward or away from the frontier). This work extends previous researchs considering public capital and human capitas as additional productive inputs and analysing its separate constribution to convergence as components of factor accumulation. In the case of human capital, we also test its rate effect as determinant factor of technical change. With this purpose we applied the Malmquist index of total factor productivity to an European data base to provide evidence for the 15 EU State Members. The results show that growth is primarily driven by factor accumulation which contribution is fundamental for lagging countries. We do not find evidence of any significant convergence over the whole period studied related to integration with factor accumulation and efficiency change as important factors of convergence while technical change (encouraged by greater human capital) has worked against it. Key words: Human Capital, Malmquist Index, Source of Convergence. JEL Classification: O47 H54 D24
Keywords: O47; H54; D24; 330; Human Capital; Malmquist Index; Source of Convergence